Prevalence and distribution of helminthic infections in India / Medasani Niveditha - Medasani, Niveditha (Запорізький державний медичний університет, 2022)
Aim: To study different types of helminthic infections in India giving a clear idea of its prevalence, distribution and high endemic areas.
Keywords: тези доповідей